The legality of banking awards - Al-Khafaf, Laila Ali (Journal of Economic, Administrative and Legal Sciences, 2018)
Banks came and prizes to be the alternative to the RIBA and took the verse (and solve Allah sale deprived RIBA) banking transactions logos, refrained from dealing with RIBA, taking and giving, and opened the doors to disciplined financial transactions rules of Sharia, which looms A promising future with the permission of Allah almighty. We should encourage and support Islamic banks and found errors and lapses, and therefore can strengthen Islamic banks fork and then measuring the foundations of Islamic economic system that rewards offered by Islamic banks are the expenses or prizes in cash or in kind